Synthesis, structures and magnetic properties of [(η9-C9H9)Ln(η8-C8H8)] super sandwich complexes - L. Münzfeld (Nature Portfolio, 2019)
Lanthanide sandwich complexes represent both a fundamental class of organometallic compounds and promising molecular magnets for information storage. Here the authors unveil a class of lanthanide sandwich complexes containing fully π-coordinated 8- and 9-membered rings, and show their slow relaxation of the magnetization.